The securitisation of values: early years leaders experiences of the implementation of the prevent strategy. Issue 4 (1st October 2020) - Anderson, Babs
ABSTRACT: This contribution examines the implementation of the 'British' values agenda within Early Childhood Care and Education (ECEC) settings in England, as introduced by the Prevent Duty. It begins by tracing the rise of the ECEC setting as the primary place of education of the young child, as this has shifted from the home environment. It examines the place of values education, culminating in the Government directive on the promotion of 'British' values, and how these values must be seen as integral to effective ECEC provision. Using a case study of two focus groups and subsequent in-depth semi-structured interviews, the implications of the introduction of this strategy are identified, focusing in particular on the relationships between the ECEC leaders and parents. This presents clear evidence of the potential for a negative impact on interpersonal professional relationships.